Biological characterization of synthesized iron nanoparticles (FeNPs) from Avicennia marina for phenol red removal - Azhagu Madhavan Sivalingam (Sensing and Bio-Sensing Research)
In this study, biosynthesized Iron oxide nanoparticles (FeNPs) were green-synthesized using polyphenol-rich Avicennia marina extract. Phytochemical screening of secondary metabolites such as flavonoids, tannins, steroids, saponins, polyphenols and GC–MS identified major twelve bioactive compounds present in (responsible for Fe3+ reduction and NP stabilization. The brown FeNPs were characterized by UV–Vis, FTIR, SEM, TEM, XRD, EDX, XPS, and EIS. SEM revealed microscale aggregates containing nanoscale domains (77.78–121.38 nm). XRD confirmed nanocrystalline Fe₃O₄ spinel structure [(220), (311), (400), (511), (440) planes]. EDX showed dominant Fe/O composition. FTIR indicated Fe3+-chelating groups (–OH, –S=O). EIS demonstrated enhanced charge transfer (C < sub>dl</sub≥ 0.146 vs. 0.034 for bare GCE). FeNPs exhibited significant antioxidant activity (DPPH/ABTS), with ethanol extract showing rapid scavenging (866.5 ± 3.5 at 1 min). Total polyphenols reached 212.47 ± 7.07 mg GAE/g extract. Dye adsorption peaked for phenol red (94.9 mg/g at pH 8), following spontaneous/exothermic thermodynamics. The removal efficiency of phenol red (PR) dye by A. marina-FeNPs decreased from 95.6 % to 54.6 % as the initial dye concentration increased from 5 mg/L to 40 mg/L. Temperature studies (25 °C, 35 °C, 45 °C) revealed that increasing temperature significantly decreased PR adsorption efficiency. Similarly, under fixed conditions (5 mg/L dye concentration, 5 g/L adsorbent dosage, pH 6.9), methylene blue (MB) removal efficiency also declined with rising temperature. Thermodynamic parameters (ΔG°, ΔH°, ΔS°) confirmed the adsorption process for both dyes was spontaneous and exothermic. EDX analysis showed the glassware contained 76.56 % iron and 17.09 % oxygen, while the synthesized iron oxide nanoparticles consisted of 46.79 % iron, 36.47 % oxygen, and 15.96 % other elements (including carbon and sulfur). These multifunctional FeNPs show promise for environmental remediation and biomedical applications.